Association of SYNTAX II Score with Immediate Outcomes in Acute ST-Segment Elevation Myocardial Infarction Patients Undergoing Primary PCI - Ali, Hassan; Nawaz, Tariq; Khan, Asfandiyar; Amin, Muhammad; Bilal, Muhammad; Khan, Muhammad Majid (Indus Journal of Bioscience Research, 2025)
Acute ST-segment elevation myocardial infarction (STEMI) is a significant health problem, which needs to be directly addressed in the attempt to regain the proper myocardial perfusion and prevent complications. Primary PCI is the preferred reperfusion therapy for STEMI, nevertheless, its outcomes are dependent on several factors such as clinical and angiographic. The most established risk scores, including TIMI and GRACE scores, barely address lesion complexity as a factor influencing procedural and post procedural consequences. The SYNTAX II score or the updated SYNTAX score is a greater blend; it going beyond clinical assessment by incentivizing specific angiographic characteristics related to STEMI patients undergoing primary PCI. Therefore, the purpose of this study was to assess the correlation of immediate post-PCI SYNTAX II scores with mortality and MACE in 124 STEMI patients burdened by multivessel CAD. There was shown statistically significant positive linear dependence between (SYS scores and mortality rate (r = 0.389, p < 0.001), and MACE (r = 0.421, p < 0.001). Subgroup analysis of the correlation between different characteristics and clinical efficacy also showed statistical significance: Elderly patients (≥60 years) and overweight patients had a stronger Correlation relationship. The results highlight the SYNTAX II score to be helpful in deciding the immediate clinical treatment strategies for the high-risk STEMI patient population. This study highlights the SYNTAX II score’s strong prognostic value in acute STEMI patients undergoing primary PCI, predicting post-interventional mortality and MACE rates. Higher scores correlate with poorer outcomes, emphasizing its role in risk assessment. Future research should explore its long-term prognostic accuracy and external validation in broader populations.